Evaluation of Lithuanian pension system reform and financial crisis implications - Gudaitis, Tadas (Publishing House of the Wrocław University of Economics, 2009)
Problem: There is no systematic assessment of Lithuanian pension system’s results. In order to prepare possible development scenarios of the reform, it is expedient to assess the extent of the pension system reform, to evaluate the performance of private pension funds and to grade the impact of reduced financing on the reform. Object: Lithuanian pension system reform. Goal: Analysis of social and economic reasons of Lithuanian pension system reform, evaluation of the results of the reform, grading the impact of reduced finance and providing possible solutions for further development of pension system reform. ethodology: comparative analysis, logical and systematic analysis of literature. The analyzed topic is actual, because achieved pension system’s results are evaluated in the initial phase of the pension system reform. Moreover, proposals, which could be successfully adapted to the subsequent development of the pension system reform, are provided in the article. The article also considers a political risk and its influence in the recent period, when financing of the pension system reform was reduced. The publications of world’s well-known social economy researchers, Lithuanian pension system reform laws and statistical data are analyzed in the article. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 198-206